1998
DOI: 10.1111/j.1398-9995.1998.tb03914.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various vacuum cleaners on the airborne content of major cat allergen (Fel d 1)

Abstract: Our results suggest that: 1) The two VCs with leakage in the experimental room had greater leakages in the apartment. 2) In the apartment with cats, all VCs provoked increases in airborne Fel d 1, primarily carried by large particles. 3) Given the increased marketing of "antiallergic" VCs, further studies are needed to standardize methods for testing airborne allergen leakage by VCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 9 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…Emission rates for cat allergen were based on studies that characterized the occurrence, suspension, and removal of cat allergen, Fel d 1 , inside homes [ 7 , 42 , 43 ]. Based on findings from those studies, we chose to model generation of cat allergen with a constant and intermittent source.…”
Section: Methodsmentioning
confidence: 99%
“…Emission rates for cat allergen were based on studies that characterized the occurrence, suspension, and removal of cat allergen, Fel d 1 , inside homes [ 7 , 42 , 43 ]. Based on findings from those studies, we chose to model generation of cat allergen with a constant and intermittent source.…”
Section: Methodsmentioning
confidence: 99%
“…In an experimental room with cat allergen present in dust, levels of allergen in air can reach y5 ng?m -3 when the room is vacuum cleaned [33]. Since the tidal volume of breathing is y8 L?min -1 , the total volume of air being ventilated during 24 h is y10 m 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in natural settings, vacuum cleaner bags may be over-full or torn, resulting in leakage of dust and mite allergens during use. Hence, caution should be exercised when recommending vacuuming as a means to control allergen load because it may inadvertently increase personal exposure to inhabitants, especially if care is not taken to ensure that vacuum cleaners with over-full or leaky dust collection bags are not used (De Blay et al, 1998). This possibility is supported by an epidemiological study on 72 homes in Tasmania, which reported that frequent vacuum cleaning of at least once a week was associated with significantly higher environmental dust-mite allergen concentrations than homes which vacuumed infrequently (Couper et al, 1998).…”
Section: Discussionmentioning
confidence: 99%